FINGERPRINTS IDENTIFICATION USING NEUROFUZZY SYSTEM - Jabber, Emad S.; Shahed, Maytham A. (Iraqi Journal for Electrical and Electronic Engineering, 2006)
This paper deals with NeuroFuzzy System (NFS), which is used for fingerprint identification to determine a person's identity. Each fingerprint is represented by 8 bits/pixel grayscale image acquired by a scanner device. Many operations are performed on input image to present it on NFS, this operations are: image enhancement from noisy or distorted fingerprint image input and scaling the image to a suitable size presenting the maximum value for the pixel in grayscale image which represent the inputs for the NFS. For the NFS, it is trained on a set of fingerprints and tested on another set of fingerprints to illustrate its efficiency in identifying new fingerprints. The results proved that the NFS is an effective and simple method, but there are many factors that affect the efficiency of NFS learning and it has been noticed that the changing one of this factors affects the NFS results. These affecting factors are: number of training samples for each person, type and number of membership functions, and the type of fingerprint image that used.